PENILAIAN KONDISI JEMBATAN DENGAN METODE NYSDOT (STUDI KASUS 3 JEMBATAN DI KOTA KENDARI) - Marsuki M., Marsuki M.; Triwiyono, Andreas; Christady, Hary (Civil Engineering Forum Teknik Sipil, 2009)
Bridge plays a vital role in supporting life activity. A lot of bridges are required due to many watercourses running from mountain that also requires a lot of amount in the budget. Neglecting such problem may lead to traffic disturbance and discomfort. The purpose of this research is to assess the bridge condition and its components, to compose the handling priority program and the bridge component priority. The research was located in Kendari of the Province of Sulawesi Tenggara. Located above Kendari Bay, a crowd economic area, Kendari has the important downtown access road. NYSDOT (New York State Department of Transportation) Method and completed with AHP (Analytical Hierarchy Process) method were used to assess the bridge condition. The bridge component scoring was calculated using the AHP method. The calculated components were compiled using the matrix of paired-comparison by referring the importance value. The, bridge component scoring consisted of three categories: (a) first category: the structural component received direct traffic load (component distributing traffic load), which was given the first priority where the importance value was higher, (b). Second category: the structural component received indirect traffic load, (c). Third category: non structural component. Calculation method AHP for every bridge component was obtained through paired-comparison. Components with bad value were found in Pasar Baru Bridge, which was rated 3 for its extension component, paving surfaces, pavement and curb. The subsequent ones were the Tripping bridge, which was rated 4 for its extension joint component and Kadia bridge which was rated 5 on its main beam, abutment, deck and back wall. Both, NYSDOT and AHP methods resulted in same assessment figures. The proposed priority handlings in subsequent order for the three bridges were Pasar Baru Bridge, Kadia Bridge and Tripping Bridge. The condition indexes were 4,514 (Average), 5,722 (Good) and 6,083 (Very Good), respectively. The proposed handlings for Pasar Baru and Kadia bridge were rehabilitation and maintenance.